Protection of civil rights and legal interests in Ukraine - Гончаренко, Влада Олександрівна; Гончаренко, В. О.; Гончаренко, Влада Александровна; Honcharenko, Vlada O.; Goncharenko, Vlada; Спасова, Катерина Іванівна; Спасова, К. І.; Спасова, Екатерина Ивановна; Spasova, Kateryna I.; Spasova, Ekaterina; Калітенко, Оксана Михайлівна; Калітенко, О. М.; et al. (Editorial Primmate S. A. S., 2019)
The article is devoted to the complex analysis of general-theoretical and practical legal issues on the protection of civil right and interests, the essence of the legal interest as a specific object of protection, determining of the ways and forms of the protection of civil right and interests and the development of the grounded suggestions and recommendations as for the improvement and effective application of the legal norms in the sphere of civil right and interests protection. The notion and essence of civil right and interests protection have been studied, the categories as "form", "way", "means" of protection have been determined, the peculiarity and possibility of the application of civil means of protection of subjective civil rights as for the protection of the legal interest have been outlined.

Стаття містить комплексний аналіз загально-теоретичних та практичних проблем захисту цивільних прав та законних інтересів, сутності законного інтересу як особливого об’єкту захисту, визначення способів та форм захисту цивільних прав та інтересів, розробку обґрунтованих пропозицій та рекомендацій щодо вдосконалення та ефективного застосування норм законодавства у сфері захисту цивільних прав та інтересів. Досліджено поняття і сутність захисту прав та інтересів, встановлено розмежування між такими категоріями як «форма», «спосіб», «засіб» захисту, визначено специфіку та можливість застосування цивільно-правових способів захисту суб’єктивних цивільних прав щодо захисту законного інтересу.
Goncharenko V. Protection of civil rights and legal interests in Ukraine / V. Goncharenko, E. Spasova, O. Kalitenko // Amazonia Investiga. – Vol. 8. – Iss. 22. – Editorial Primmate S. A. S., 2019. – P. 135-140.
Keywords: defense of rights and interests; the forms of protection; legal interest; the means of protection; protection of civil rights and legal interests; the right of protection; право на захист; захист цивільних прав та інтересів; охорона прав та інтересів; законний інтерес; способи захисту; форми захисту; Research Subject Categories::LAW/JURISPRUDENCE